New valves - new dangers?: 22 valves (38 probes) designed in the 'Nineties in ultralong-term tests (365 days) - Oikonomou, J.; Aschoff, Alfred; Hashemi-Kalibar, Seyed-Bahram; Kunze, Stefan (European journal of pediatric surgery, 1999)
Thieme E-Books & E-Journals
Gesehen am 05.05.2021